Three new species of Aspalathus (Crotalarieae, Fabaceae) from the Cape Floristic Region of South Africa - Stirton, Charles Howard; Preez, Brian Du; Euston-Brown, Douglas I. W.; Muasya, A. Muthama (Phytotaxa, 2025)
We describe and illustrate three species of Aspalathus from the poorly explored Baviaanskloof Biosphere Reserve, and the Klein Swartberg mountains of South Africa as new: Aspalathus chlorina C.H.Stirt. & Muasya, A. vulpicaudata C.H.Stirt. & Muasya, and A. outrampsii C.H.Stirt. & Muasya. IUCN red data list assessments are also provided, along with a distribution map and notes on ecology.